The SYSTEM IDENTIFICATION OF FRIEND AND ENEMY USING NIGHT VISION CAMERA ON BATTLE ROBOT (CQB) USING PATTERN RECOGNITION METHOD - Pratama, Eko Wahyu; Ansori, Mohammad; Suryadi, Kusno (Jurnal Elkasista, 2021)
Abstract – Indonesian Army has the main task of protecting against enemy attacks, which include forest battles as well as urban battles. The obstacle faced today is that in the process of urban warfare operations, infiltration and hostage rescue in buildings are still less efficient and optimal. The robot is designed with a system that can identify friends and foes using a Night Vision camera and the Pattern Recognition method. Pattern recognition is a symbolic grouping automatically that is done by a computer to find out objects or patterns. The results of the Night vision camera test are able to detect human objects with a maximum distance of 6 meters. This night vision scope has a fairly large accuracy rate of 83%. And light intensity has an influence on the identification process because if the light intensity is more than 200 lux then the system is not able to identify the object.